HYDRAULIC DYNAMICS OF THE REGOLITHIC NEOSOL IN THE CERRADO OF THE SERRA DA CANASTRA NATIONAL PARK-MG - Confessor, Jefferson Gomes; Silva, Lara Luiza; Rodrigues, Silvio Carlos (Ra'e Ga: o Espaço Geográfico em Análise, 2024)
The knowledge of soil water dynamics, as elements are added, removed, and transformed, is an aid to understanding the processes at play in landscapes. Understanding the functioning of natural environments not only contributes to comprehending the natural dynamics of systems but also serves as a reference for adopting measures in areas at different stages of degradation. In this sense, this study sought to analyze the physical/hydraulic characteristics of the Regolithic Neosol in the Serra da Canastra National Park, MG. For this purpose, two different models of field infiltrators were used: namely a rain simulator and a concentric ring infiltrometer. Results involving the use of a rain simulator indicated high soil infiltration capacity (99.31%) even when subjected to high-intensity events (57.4 mm/h). The ring infiltrometer revealed high values of basic infiltration velocity (317.58 mm/h). These values indicate that despite being shallow (20 cm), the soil, characterized by coarse material (sand and lateritic gravel), has a high capacity to incorporate water precipitated into the profile, generating subsurface lateral flows between the higher and lower parts of the slope and causing the movement of iron along with underground water flow.